[PP.22.23] VASCULAR ENDOTHELIAL GROWTH FACTOR RECEPTOR INHIBITION INDUCES VASCULAR DYSFUNCTION VIA REDOX-SENSITIVE AND NITRIC OXIDE-DEPENDENT PATHWAYS. (September 2017) - Neves, K.; Rios, F.; Montezano, A.; Van Der Mey, L.; Small, H.; Savoia, C.; Touyz, R.
Abstract : Objective: Vascular endothelial growth factor (VEGF)/ VEGF receptor (VEGFR) inhibitors, used as anti-angiogenic drugs to treat cancer, induce severe hypertension. Molecular mechanisms whereby VEGF inhibitors cause hypertension are unclear, but nitric oxide (NO) and oxidative stress may be involved. We questioned whether reactive oxygen species (ROS), important regulators of vascular function in hypertension, also play a role in VEGF inhibitor-induced vascular dysfunction. Design and method: Human microvascular endothelial cells (HMECs) were stimulated with vatalanib (VEGFR inhibitor) and gefitinib (EGFR inhibitor). Normotensive male SV-129 mice were treated with Vatalanib (100 mg/Kg/day) or Gefitinib (100 mg/Kg/day). Vascular reactivity was performed in mesenteric arteries. Phosphorylation of eNOS was assessed by immunoblotting. ROS were measured by amplex red, lucigenin and nitrotyrosine elisa. TBARS levels were measured by lipid peroxidation assay kit and catalase activity by amplex red. Nox and antioxidant enzymes mRNA was analysed by qPCR. Results: No changes in blood pressure were observed in animals treated with vatalanib on this dose. However acetylcholine-induced vasodilatation was impaired in those mice and phosphorylation of eNOS activation site (Ser1177) was decreased, while no changes were observed after exposure of HMECs to gefitinib. Hydrogen peroxide (H2O2) levels were reduced in HMECs stimulated with vatalanib and in aorta and heart from vatalanib-treated mice. This effect was followed by an increase in catalase activity and a decrease in Nox 4 mRNA expression while Nox5 mRNA levels were increase by vatalanib. VEGF inhibition also increased peroxynitrite levels in aorta and kidney and increased plasma TBARS levels. In kidney vatalanib increased H2O2 and superoxide anion production which was followed by a decrease in catalase activity and Nrf2 nuclear translocation. mRNA levels of antioxidant enzymes in HMECs, kidney and heart were decreased after exposure to vatalanib. Gefitinib only increased catalase activity and peroxynitrite levels in heart as well as decreased Nrf2 nuclear translocation in kidney from mice. Conclusions: In conclusion, our data identify novel mechanisms whereby VEGFR inhibition modulates NO signalling, antioxidant defences and ROS production in tissues and endothelial cells. These molecular processes may contribute to reduced vasorelaxation and may play a role on VEGFRI-induced hypertension.